(untitled) (International Journal of Current Research in Physiology and Pharmacology, 2022)
Background: Sweeteners are a utile source of nourishment for cuisine preparation but are linked with the risk of occurrence of several diseases. Hence, the quest for healthier sweetening agents with lesser harmful effects cannot be ignored. Saccharum officinarum molasses, a natural nutritive sweetener, has become a popular substitute despite a dearth of knowledge on its healthiness. Aim: To assess the effects of Saccharum officinarum molasses on hematology, serum electrolyte, lipid profile, liver histology, and redox status of male Wistar rats. Methods: Blackstrap® Saccharum officinarum molasses (SOM) was fractionated to obtain Saccharum officinarum molasses methanol fraction (SOMMF) and Saccharum officinarum molasses aqueous fraction (SOMAqF). Seven groups (n = 5) of adult male Wistar rats received distilled water (Control); 1.0, 3.2, 10.0 g/kg SOMMF and 0.6, 2.0, 6.4 g/kg SOMAqF, respectively. Administrations were done daily via oral gavage for eight weeks. Full blood indices were determined with an automated hematology analyzer, serum electrolyte by monoliquid colorimetric test, and serum lipid profile using the enzymatic colorimetric test. Liver malondialdehyde and antioxidant levels were assayed by spectrophotometry. Liver histology was assessed using microscopy. Data were analyzed using ANOVA at p < 0.05 significance. Results: SOM increased liver catalase activity and serum levels of iron and potassium. It reduced serum levels of lipid profile, zinc and sodium ions, hemoglobin concentration, red blood cell count, packed cell volume, superoxide dismutase activity of the liver, and concurrently disrupted liver cytoarchitecture. Conclusion: Saccharum officinarum molasses adversely disrupted the hematological and hepatic functions of male Wistar rats.